Snakin/GASA proteins: Involvement in hormone crosstalk and redox homeostasis - Nahirñak, Vanesa (Landes Bioscience, 2012)
Snakin/GASA proteins are widely distributed among plant species. They are expressed in different plant organs with high tissue and temporal specificity, and their subcellular localization varies among the different members. Interestingly, all of them maintain 12 cysteines of the C-terminus in highly conserved positions of the aminoacid sequences that are essential for their biochemical activity and probably responsible for their protein structure. Despite their common features, their functions are not completely elucidated and little is known about their mode of action. This review focuses on the current knowledge about this intriguing family of peptides and advances comprising gene regulation analyses, expression pattern studies and phenotypic characterization of mutants and transgenic plants. Furthermore, we discuss the roles of Snakin/GASA proteins in several aspects of plant development, plant responses to biotic or abiotic stress and their participation in hormone crosstalk and redox homeostasis.